Effect of the heat flux direction on electrical properties of SrBi2Nb2O9 thin films crystallized using a microwave oven - Vasconcelos, J. S.; Vasconcelos, NSLS; Zanetti, S. M.; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2004)
Ferroelectric SrBi2Nb2O9 (SBN) thin films were prepared by the polymeric precursors method and deposited by spin coating onto Pt/Ti/SiO2/Si substrate and crystallized using a domestic microwave oven. It was studied the influence of the heat flux direction and the duration of the thermal treatment on the films crystallization. An element with high dielectric loss, a SiC susceptor, was used to absorb the microwave energy and transfers the heat to the film. Influence of the susceptor position to the sample crystallization was verified, the susceptor was, placed or below the substrate or above the film. The SBN perovskite phase was observed after a thermal treatment at 700 degreesC for 10 min when the susceptor was placed below the substrate and for 30 min when the susceptor was placed above the film. Electrical measurements revealed that the film crystallized at 700 degreesC for 10 min, with the susceptor placed below the film, presented dielectric constant, dielectric loss, remanent polarization and coercive field of, 67, 0.011, 4.2 muC/cm(2) and 27.5 kV/cm, respectively. When the films were crystallized at 700 degreesC for 30 min, with the susceptor placed above the film, the dielectric constant was 115 and the dissipation factor was around of 0.033, remanent polarization and coercive field were 10.8 muC/cm(2) and 170 kV/cm, respectively. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: ferroelectric; SBN; thin films; microwave